Hyperprogressive disease in patients with non‐small cell lung cancer treated with nivolumab: A case series. Issue 12 (17th October 2018) - Kanazu, Masaki; Edahiro, Ryuya; Krebe, Hiroyuki; Nishida, Kohei; Ishijima, Mikako; Uenami, Takeshi; Akazawa, Yuki; Yano, Yukihiro; Yamaguchi, Toshihiko; Mori, Masahide
Abstract : Background: Nivolumab is an anti‐PD‐1 blocking monoclonal antibody approved for the treatment of non‐small cell lung cancer (NSCLC). However, some patients on immunotherapy may experience rapid progression and worsening clinical status, known as hyperprogressive disease. We retrospectively reviewed the clinical records of patients with NSCLC administered nivolumab therapy at Toneyama National Hospital, Japan, from January 2016 to January 2018. Of the 87 patients administered nivolumab therapy, five experienced rapid progression during one cycle of nivolumab therapy. Four patients were treated with corticosteroids to overcome their symptomatic events. Nivolumab exhibited efficacy after temporal progression, so‐called "pseudoprogression", in three patients, and their symptoms and laboratory results improved. In the other patient, pleural and pericardial effusions increased after nivolumab therapy, and drainage was required, with no subsequent recurrence. The clinical courses of our case series indicate that alternative treatment, namely high‐dose corticosteroids, antibiotics, and drainage, effectively treated the symptoms of rapid tumor progression. Of note, corticosteroids suppressed the temporary inflammatory reaction to nivolumab. Although hyperprogressive disease is thought to be associated with poor quality of life and survival, these treatment strategies may be useful in patients with expected responses to immunotherapy.